2018
DOI: 10.1126/scitranslmed.aan8405
|View full text |Cite
|
Sign up to set email alerts
|

Circulating T FH cells, serological memory, and tissue compartmentalization shape human influenza-specific B cell immunity

Abstract: Immunization with the inactivated influenza vaccine (IIV) remains the most effective strategy to combat seasonal influenza infections. IIV activates B cells and T follicular helper (T) cells and thus engenders antibody-secreting cells and serum antibody titers. However, the cellular events preceding generation of protective immunity in humans are inadequately understood. We undertook an in-depth analysis of B cell and T cell immune responses to IIV in 35 healthy adults. Using recombinant hemagglutinin (rHA) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
215
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 212 publications
(241 citation statements)
references
References 38 publications
23
215
0
Order By: Relevance
“…Using fluorochrome labeled tetramer or monomer reagents, hemaggulutinin (HA)-specific Bmems have been identified within one month after IIV. 1921 This antigen-specific Bmem compartment after IIV has been described as heterogeneous, comprising typical and atypical memory B cells. 1921 We wanted to assess the phenotype and kinetics of the HA-specific Bmem compartment after IIV and the relationship of this compartment to the plasmablast and long-lived antibody (Ab) response.…”
Section: Resultsmentioning
confidence: 99%
“…Using fluorochrome labeled tetramer or monomer reagents, hemaggulutinin (HA)-specific Bmems have been identified within one month after IIV. 1921 This antigen-specific Bmem compartment after IIV has been described as heterogeneous, comprising typical and atypical memory B cells. 1921 We wanted to assess the phenotype and kinetics of the HA-specific Bmem compartment after IIV and the relationship of this compartment to the plasmablast and long-lived antibody (Ab) response.…”
Section: Resultsmentioning
confidence: 99%
“…Since then, subsets of CD4 + T cells with "Tfhlike" characteristics, frequently referred to as circulating Tfh (cTfh) increase of a CXCR3+ population of cTfh cells that correlates with increase in high-avidity antibodies. 112,113 Induction of cTfh cells has also been observed in volunteers receiving in-trial HIV vaccines and a novel Escherichia coli vaccine. [114][115][116] Patients with autoimmunity such as systemic lupus erythematosus, rheumatoid arthritis, and Sjögren syndrome have increased frequency of cTfh cells with an "activated" phenotype which correlates with disease activity.…”
Section: Tfh Cell S In the B Loodmentioning
confidence: 99%
“…Tfh1 cells are also present outside the GCs in human tonsils [52], and Tfh1 cells therefore might interact with naïve B cells outside GCs and promote their differentiation toward CD11c + DN B cells. Studies on influenza vaccines showed that an increase of activated Tfh1 cells in the blood correlated with the emergence of CD27 + CD38 + PBs in the blood [53] as well as a precursor of ASCs sharing properties with CD11c + DN B cells (though CD27 + ) [54,55], further supporting the potential role of Tfh1 cells in the generation of ASCs and CD11c + DN B cells [56]. Intriguingly, a recent study showed that exaggerated activity of Tfh2 cells co-expressing IL-21 and IL-4 is involved in SLE pathogenesis [57].…”
Section: Cd4 + T-cell Subsets Promoting the Cd11c + Dn B Cell Activitymentioning
confidence: 99%